La importancia del intervalo de la floración en el mejoramiento para la resistencia a sequía en maíz tropical - Bolaños, J.; Edmeades, G. O. (Agronomía Mesoamericana, 2016)
The length of the Interval between anthesis and silking (ASI) is increased by drought which coincides with flowering. Four elite CIMMYT lowland tropical populations are undergoing recurrent selection (S1 or full-sib) for improved grain yield and several other traits under drought and well watered conditions. Data collected from more than 200 families per population grown In single row plots under three water stress levels (pre and post-flowering stress; post-flowering stress; normal irrigation, all in the absence of rain) showed weak or no correlation between grain yield and traits related to plant water status, such as leaf rolling and senescence, photooxidation, leaf chlorophyll concentration, shoot elongation rate, canopy temperature and predawn water potential. Yield under all levels of stress was significantly negatively correlated with AST, and as AST increased due to drought, kernels and ears per plant were significantly reduced. In all populations yield decreased by approximately 10 % per day increase in AST up to 8 days. In several stress situations broad-sense heritability of AST was greater than that of grain yield and the genetic correlation between grain yield and AST approached -1.00. Synthetics formed from one population following bidirectional selection and tested under drought showed adaptive advantage of cool canopy temperature, delayed leaf senescence, reduced AST and erect leaves, especially when all were combined with grain yield in a single index during selection. Selection for reduced AST and high grain yield under drought can be an effective means of improving drought tolerance in tropical maize.